2009
DOI: 10.4110/in.2009.9.3.98
|View full text |Cite
|
Sign up to set email alerts
|

Cordycepin Suppresses Expression of Diabetes Regulating Genes by Inhibition of Lipopolysaccharide-induced Inflammation in Macrophages

Abstract: BackgroundIt has been recently noticed that type 2 diabetes (T2D), one of the most common metabolic diseases, causes a chronic low-grade inflammation and activation of the innate immune system that are closely involved in the pathogenesis of T2D. Cordyceps militaris, a traditional medicinal mushroom, produces a component compound, cordycepin (3'-deoxyadenosine). Cordycepin has been known to have many pharmacological activities including immunological stimulating, anti-cancer, and anti-infection activities. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
37
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 33 publications
5
37
0
1
Order By: Relevance
“…In this study, we demonstrated that cordycepin prevented IL-1β-induced NO production as well as iNOS expression at the mRNA and protein levels in human OA chondrocytes. Results were consistent with Seulmee et al's results [17]. They found that cordycepin could inhibit NO production as well as iNOS expression on lipopolysaccharide-induced inflammation in RAW 264.7 cells.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, we demonstrated that cordycepin prevented IL-1β-induced NO production as well as iNOS expression at the mRNA and protein levels in human OA chondrocytes. Results were consistent with Seulmee et al's results [17]. They found that cordycepin could inhibit NO production as well as iNOS expression on lipopolysaccharide-induced inflammation in RAW 264.7 cells.…”
Section: Discussionsupporting
confidence: 92%
“…Our results were consistent with the research from Noh et al [16], who found no significant change RA synovial fibroblast cell viability following treatment with cordycepin (50 uM or 100 uM). Also, Seulmee et al [17] showed that the exposure of mouse leukaemic monocyte macrophage cell line (RAW 264.7) to cordycepin at 5∼40 μg/ml for 24 hours showed no significant adverse effect on cell viability versus the untreated control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cordycepin is extracted from fungi of genus Cordyceps, and has been used traditionally as an anti-tumor, anti-viral, anti-inflammatory agent in East Asian countries (21)(22)(23)(24)(25)(26). In this study, we examined the inhibitory effect of cordycepin on the melanogenesis signaling pathways, including the expression of MITF, tyrosinase, TRP1 and TRP2, and the phosphorylation of CREB, via the activation of ERK and Akt in murine B16F10 melanoma cells stimulated by α-MSH and IBMX.…”
Section: Introductionmentioning
confidence: 99%
“…In China, it has been used as a traditional medicine and health food since ancient times. C. militaris has been reported to have beneficial functional effects such as anti-angiogenesis, 6) anti-tumor, anti-diabetic 7) , and hypoglycemic effects 8) . Cordycepin, a characteristic functional component of C. militaris, has been shown to have anti-inflammatory effects.…”
mentioning
confidence: 99%